2015
DOI: 10.1007/978-3-319-20349-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Brief Review of Liquid Crystals

Abstract: Examined and summarized the types of liquid crystals. Analyzed structural characteristics of smectic, nematic and cholesteric liquid crystals. It is noted that cholesteric liquid crystals are helically twisted structure, the pitch of the helix which is temperature dependent and individual chemical properties of liquid-crystalline compounds of cholesterol. Results on the influence of temperature on rheological properties of cholesteric liquid crystals are presents.This chapter describes briefly main ideas of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…In addition to ordering on the center-of-mass positional level, quasi-long ranged orientational ordering is possible, yielding the so-called nematic phase. 15,16 Two obvious pairwise properties to compute from the configurational data of hard ellipses are center-of-mass distances and the relative orientations of the ellipses. With respect to the former, we use the positional features with a single probe particle as employed in Paper I for hard disks and spheres.…”
Section: Hard Ellipsesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to ordering on the center-of-mass positional level, quasi-long ranged orientational ordering is possible, yielding the so-called nematic phase. 15,16 Two obvious pairwise properties to compute from the configurational data of hard ellipses are center-of-mass distances and the relative orientations of the ellipses. With respect to the former, we use the positional features with a single probe particle as employed in Paper I for hard disks and spheres.…”
Section: Hard Ellipsesmentioning
confidence: 99%
“…Here, we seek to generalize the formalism developed in Paper I to assess its utility for detecting phase transitions in a broader class of systems. Examples include equilibrium systems with 1) anisotropic particles leading to orientational as well as positional ordering 15,16 and 2) compositional degrees of freedom that can induce demixing, even in the absence of appreciable density fluctuations. 17 We also address active or driven matter, which exhibits phase transitions whose detection and characterization cannot generally be facilitated based on arguments from equilibrium statistical mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that utilization of 4-HMF might find a broad application in the synthesis of 2,4-substituted furan compounds used in pharmaceutical and material industries [6] (Figure 1, right). 4-HMF could be upgraded into other valuable platform compounds such as 2,4-bis(hydroxymethyl)furan (2,4-BHF) (the precursor of calcineurin inhibitor [21]), 4-(hydroxymethyl)furan-2-carboxylic acid (4-HMF-2-CA) (which could convert to prostaglandin receptor EP4 [22]), furan-2,4-dicarboxylic acid (2,4-FDCA) (which could convert to liquid crystal materials) [23],[24], and ( E )-5-(3-ethoxy-3-oxoprop-1-enyl)furan-3-carboxylic acid (EOEFCA) (the precursor of photo cross-linking of copolymer) [6].…”
Section: Introduction Of Hmfsmentioning
confidence: 99%
“…Some organic substances pass from crystaline, solid to isotropic, liquid states, not directly, but through a phase [1,2]. The mechanical and symmetrical properties of these phases are intermediate to the properties of liquids and crystals [3,4]. Because of this, these substances are called liquid crystals or liquid anisotropic crystals.…”
Section: Introductionmentioning
confidence: 99%